Islamic urban heritage in Constantine - challenges and prospects - Khalfallah, Boudjemaa; Derbal, Kaddour (Technium Social Sciences Journal, 2023)
Scientific research on heritage is many and varied , because it represents a collective historical and cultural repository that expresses essentially identity. Among the areas of heritage, we distinguish the urban and architectural heritage that reflects the true identity and the civilizational dimension, which today the process of preserving it has become a historical responsibility and a national and national duty that stops specialists in all parts of the world. In light of the growing interest in the concept of sustainable development in various fields, the care of heritage in its comprehensiveness emerges as one of the major axes of this development, and an area that falls within the framework of a comprehensive policy to preserve the diverse world heritage. There is no doubt that the general problem with regard to ancient urban tissues lies in their ability to respond to the modern requirements of architectural urban development and provide an environment in which the balance between man and his surroundings is not disturbed, and to preserve the prevailing social and human dimensions, and to overcome purely economic approaches in comparing modern projects and conservation projects. In this context, we have the right to ask whether it is possible to protect and breathe life into heritage urban tissues, without this being an attempt at temporary revival. Is it possible to achieve sustainable urbanization in light of the predominance market rules? This research mainly aims to visualize an urban project that aims to achieve two basic things: - Protecting the Arab-Islamic architectural and urban identity of the city of Constantine, the capital of eastern Algeria, which has been subjected to cultural obliteration and attempts at Westernization over more than a century of French colonialism. - Adopting a practical methodology during the course of the approach